Effect of nanoparticles on the durability of cement stabilised base course materials - Rezagholilou, Alireza (Curtin University, 2015)
The laboratory experiments in this research have yielded results in the form of a numerical evaluation of the wet/dry cycle test method, a suggestion of the post-carbonation time dependent relationships for resilient modulus, and the strength of cement modified CRB material designed according to Australian codes. The microstructural effects of nano silica and carbonation on hydration products in such mixes were also investigated by means of Scanning Electron Microscopy (SEM).